Neutrinos, majorons and dark matter models in astroparticles physics - Arbelaez - Rodriguez; Carolina (2023)
2 The discovery of the Higgs-like resonance by the ATLAS and CMS represents a big success for particle physics and completes the Standard Model elementary spectrum. Nevertheless, and mh ? 125 GeV elementary Higgs neither solves the hierarchy problem, nor does it provide a dynamical mechanism of electroweak symmetry breaking. Composite Higgs models have the potential to provide a solution to the hierarchy problem and a dynamical explanation for the generation of the Higgs potential. These models can be tested at the LHC as the new sector which underlies electroweak symmetry breaking must become strong in the TeV regime, which implies additional bounds states beyond the Higgs. This represents also a very promising topic to board during my academic research. PARCIAL The analysis and study of a model based on a composite SO(5)/SO(4) Higgs model is a work in progress that we expect to publish at the end of the present year. 3 The Earth is permanently bombarded by cosmic rays coming from many astrophysical objects (the Sun, supernovae, supermassive black holes in the center of far away galaxies). At ground level, about fifteen million particles impact every square meter every day. In order to study the most evasive phenomena of the Universe, the scientific community is building and updating laboratories that will allows scientists to study weak interacting particles, neutrinos and dark matter. Considering all this appealing and exciting progress in the physics community (in particular in Latinoamerica) and also the several interesting and challenging open questions and puzzles, I will encourage myself to propose models with could be tested at actual and future experiments. TOTAL The topics explore this proposal represent frontier physics. For the models studied there are some experimental prospects of testing these by current experiments and future experiments, as for instance, LHC. 4 Keep and enforce some fruitful academic collaborations established during my research period, including the PhD and postdoctorate: with ...